Virus Infection-Induced Bronchial Asthma Exacerbation - Mutsuo Yamaya (Pulmonary Medicine)
Infection with respiratory viruses, including rhinoviruses, influenza virus, and respiratory syncytial virus, exacerbates asthma, which is associated with processes such as airway inflammation, airway hyperresponsiveness, and mucus hypersecretion. In patients with viral infections and with infection-induced asthma exacerbation, inflammatory mediators and substances, including interleukins (ILs), leukotrienes and histamine, have been identified in the airway secretions, serum, plasma, and urine. Viral infections induce an accumulation of inflammatory cells in the airway mucosa and submucosa, including neutrophils, lymphocytes and eosinophils. Viral infections also enhance the production of inflammatory mediators and substances in airway epithelial cells, mast cells, and other inflammatory cells, such as IL-1, IL-6, IL-8, GM-CSF, RANTES, histamine, and intercellular adhesion molecule-1. Viral infections affect the barrier function of the airway epithelial cells and vascular endothelial cells. Recent reports have demonstrated augmented viral production mediated by an impaired interferon response in the airway epithelial cells of asthma patients. Several drugs used for the treatment of bronchial asthma reduce viral and pro-inflammatory cytokine release from airway epithelial cells infected with viruses. Here, I review the literature on the pathogenesis of the viral infection-induced exacerbation of asthma and on the modulation of viral infection-induced airway inflammation.